Technique de mon langage musical: Texte avec exemples musicaux - Messiaen, Olivier 1908-1992 (Paris Alphonse Leduc, 1944)
In 1944, Messiaen offered a systematic description of his musical language in a text entitled Technique de MonLangage Musical, an exposition of his compositional techniques that represents one of the most important accountsof his musical thoughts. This text is important not only in understanding his methods of composition, but also incomprehending the multiplicity and variety of his aesthetic ideas. In spite of the large variety of sources that inspireit, in Technique, Messiaen presents a compositional thought that, at least in part, proves to be substantially cohesive.The purpose of this paper is to describe the content of the Technique, with particular attention to aspects concerningrhythm and harmony, which are the elements that received Messiaens deepest attention and which also had thegreatest influence on later 20th-century composers.
Keywords: Composing